Challenges for providing health care in traumatized populations: barriers for PTSD treatments and the need for new developments - Evaldas Kazlauskas (Taylor & Francis Group, 2017)
There is a growing recognition about the effects of traumatic experiences on mental health worldwide. With ongoing conflicts, natural disasters, interpersonal violence, and other traumatic events it is estimated that approximately 70% of the global population have been exposed to at least one lifetime traumatic experience. Research shows a substantial proportion of survivors, especially in low- and middle-income countries, would have a posttraumatic stress disorder (PTSD). During recent decades effective evidence-based treatments for PTSD have been developed. However, there are significant barriers to mental health services and trauma-informed treatments are not easily available for trauma survivors. From the perspective of social psychotraumatology several core barriers to trauma treatments were identified, including the lack of acknowledgment, and avoidance of disclosure. The need for cultural sensitivity in PTSD treatments, the potential of alternative ways of treatment delivery, and the involvement of non-professional volunteers are proposed as directions for future developments in the field.